Leaders as cognitive shortcuts: on the representation of political competition at the European elections of 2014 in Italy. Issue 3 (1st September 2016) - Camatarri, Stefano; Cavataio, Mariano
ABSTRACT: The huge success of the Democratic Party at the last European Parliament (EP) election in Italy has been widely interpreted as due to the unusual ability of its new leader Matteo Renzi to mobilize support for his party in an era of candidate-oriented and valence politics in which political leaders' personal characteristics are crucial for vote choices and party performances. Framing the last EP elections as a sign of the overwhelming importance of personalized politics and personalized voting, however, does not tell us everything, there is to know about the role of leaders in voters' decisions. According to the literature, in fact, leaders are not only a collection of personal traits and characteristics exerting short-term effects on voting behaviour, but also cognitive shortcuts that help decision-making by simplifying the complexity of the political environment. Within this framework, we investigate whether leader evaluations, in the form of confidence ratings, provide information about how Italian voters perceived the structure of political debate at the 2014 EP elections. Our results confirm that judgments of leaders imply specific representations of political competition, of which we try to outline some general features.